Current controlled negative differential resistance behavior in Co2FeO2BO3 and Fe3O2BO3 single crystals. (March 2016) - dos Santos, E.C.; Freitas, D.C.; Fier, I.; Fernandes, J.C.; Continentino, M.A.; de Oliveira, A.J.A.; Walmsley, L.
Abstract: I – V curves showing negative differential resistance (NDR) are reported for single crystals of Co2 FeO2 BO3 at 315 K and 290 K and for Fe3 O2 BO3 at 300 K, 260 K and 220 K. Resistivity measurements are presented for both systems, parallel and perpendicular to the c axis, in the range 315–120 K. The high hysteretic behavior of the I – V curves in Co2 FeO2 BO3 around room temperature is discussed and the heat dissipated is estimated, suggesting an increase in the sample temperature of almost 22 K for the I – V curve at 315 K and a dominant contribution of Joule self-heating for the observed NDR. In contrast, insignificant hysteresis is observed on the I – V curves of Fe3 O2 BO3 around room temperature. The depinning of charge order domains is suggested as the main contribution to the NDR phenomenon for Fe3 O2 BO3 . The high reproducibility of the NDR in the Fe3 O2 BO3 single crystal allows its use as a low frequency oscillator, as it is demonstrated. Highlights: I – V curves show negative differential resistance in the room temperature range. A highly hysteretic behavior is seen on I – V curves in the single crystal of Co2 FeO2 BO3 . A thermal analysis is done to quantify the Joule heating in Co2 FeO2 BO3 . In contrast with Co2 FeO2 BO3, I – V curves of Fe3 O2 BO3 show no significant hysteresis. Charge order depinning can explain the I – V curves in Fe3 O2 BO3, used in an oscillator.